y = x + 4/x
replace x with -x. Do you get back the original equation after simplifying. if you do, the function is even.
replace y with -y AND x with -x. Do you get back the original equation after simplifying. If you do, the function is odd.
A function can be either even or odd but not both. Or it can be neither one.
Let's first replace x with -x
y = -x + 4/-x = -x - 4/x = -(x + 4/x)
we see that this function is not the same because the original function has been multiplied by -1
. Let's replace y with -y and x with -x
-y = -x + 4/-x
-y = -x - 4/x
-y = -(x + 4/x)
y = x + 4/x
This is the original equation so the function is odd.
Answer:
b the second 1
Step-by-step explanation:
Answer:
(0, - 3 ) and (- 1, - 5 )
Step-by-step explanation:
Given the 2 equations
y = 4x² + 6x - 3 → (1)
y = 2x - 3 → (2)
Substitute y = 4x² + 6x - 3 into (2)
4x² + 6x - 3 = 2x - 3 ( subtract 2x - 3 from both sides )
4x² + 4x = 0 ← factor out 4x from each term
4x(x + 1) = 0
Equate each factor to zero and solve for x
4x = 0 ⇒ x = 0
x + 1 = 0 ⇒ x = - 1
Substitute these values into (2) for corresponding values of y
x = 0 : y = 2(0) - 3 = 0 - 3 = - 3 ⇒ (0, - 3 )
x = - 1 : y = 2(- 1) - 3 = - 2 - 3 = - 5 ⇒ (- 1, - 5 )
Answer:
Step-by-step explanation:
Use the change-of-base rule.
Answer:
y intercept is -5 and slope is 6/1
Step-by-step explanation: